THE LINKAGE BETWEEN STRATEGIC HUMAN RESOURCE MANAGEMENT AND ORGANIZATIONAL PERFORMANCE THROUGH EMPLOYEE RELATIONS AS AN INTERVENING VARIABLE AT PT. BORWITA CITRA PRIMA MANADO - Pesik, Rebecca; Pangemanan, Sifrid S.; Tumewu, Ferdinand J. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: A distributor company was established to provide products and services that are needed by the consumers. To perform good activities of distribution, human resource management is required to carry out their job and responsibilities. Strategic human resource management is important in managing human resources in order to determine the success of a company. This study aims to analyze the linkage between SHRM and Organizational Performance through Employee Relations as an intervening variable. This research is using quantitative research method, Population in this research is the all permanent employees in PT Borwita Citra Prima Manado with the sample size are 67 samples. Path analysis was used to measure the causal relationship between SHRM and organizational performance and employee relations as mediation. This research used sobel test to measure the indirect effect. The result of this research revealed there are positive relationship between SHRM toward organizational performance and employee relations as an intervening variable in PT. Borwita Citra Prima Manado. In this research is categorized as partially mediation effect. The company should reconsider to give appreciation for employees who work on time or employees who have low rate absenteeism and more maintain the stability of employee relations to reduce the employee?s interpersonal conflict. Keywords: strategic human resource management, organizational performance, employee relations.